C# 2012 fundamentals livelessons (sneak peek video training). Parts I, II, III, and IV - Deitel, Paul.; Safari eBooks ([S.l.] : Prentice Hall, 2013)
"C# 2012 Fundamentals LiveLessons presents Paul Deitel's signature "Live Code" treatment of Microsoft's C# 2012 programming language - over 40 hours of expert video! Every important C# concept is presented in the context of a complete, working C# 2012 program. This LiveLesson contains over 20,000 lines of fully tested C# program code. And developers are free to reuse all of it. Among the key topics included in this LiveLesson are: Windows 8 UI: Windows 8 UI style apps are called Windows Store apps. In Lesson 25, Deitel shows how to create and test Windows Store apps and upload them to Microsofts Windows Store. Databases and LINQ to Entities: The LINQ to SQL technology covered in the previous edition has been replaced with the more robust LINQ to Entities and the ADO.NET Entity Framework; Microsofts free SQL Server Express 2012 is used to present the fundamentals of database programming; ASP.NET 4.5, Microsofts .NET server-side technology, enables developers to create robust, scalable web-based apps; Windows Phone 8, Microsofts latest operating system for smartphones. It features multi-touch support for touchpads and touchscreen devices, enhanced security features and more. In Lesson 27 the author builds a complete working Windows Phone 8 app and test it in the Windows Phone simulator; Windows Azure, Microsoft's cloud computing platform that allows you to develop, manage and distribute apps in the cloud. Lesson 31 shows how to build a Windows Azure app; Asynchronous programming with async and await. Asynchronous programming is simplified in Visual C# 2012 with the new async and await capabilities."--Resource description page.
Title from resource description page (viewed June 13, 2013).
Presenter, Paul Deitel.
Keywords: C# (Computer program language); Electronic books